The Community Satisfaction at the Office of Lubuk Kebur Urban Village in Seluma Kota Sub-District - Murmansa Putra; Ermy Wijaya; Rinto Noviantoro (Journal of Indonesian Management, 2021)
This study aims to find out the community satisfaction at the office of Lubuk Kebur Urban Village in Seluma Kota Sub-District. The data analysis technique used is the measurement of the Community Satisfaction Index based on the Regulation of the Minister of Administrative Reform and Bureaucratic Reform Number 14 of 2017. The sample in this study was 370 people from Lubuk Kebur Village who received services from the office of Lubuk Kebur Urban Village in Seluma Kota Sub-District. The Community Satisfaction Index for service quality at the office of Lubuk Kebur Urban Village in Seluma Kota Sub-District, obtained an average value of 3.01 which was in a good assessment. Furthermore, the Community Satisfaction Index service unit is multiplied by 25 therefore the the Community Satisfaction Index at the office of Lubuk Kebur Urban Village in Seluma Kota Sub-District is 75.25 with service quality B with good criteria because it is in the interval value of 62.51 – 81.25. The element of cost/tariff gets the highest rating with an average value of 3.40 with very good assessment criteria. This illustrates that the community assesses that the office of Lubuk Kebur Urban Village in Seluma Kota Sub-District provides services for free without being charged. The lowest satisfaction value is 2.44, namely the completion time with poor assessment criteria. This illustrates that the time required for the completion of the document is not as promised, due to the slowness of employees in providing services, insufficient requirements and the Urban Village Head who is is often not there.